2014
DOI: 10.1016/j.cmet.2013.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolomics Reveals Endogenous Ligands of DAF-12, a Nuclear Hormone Receptor, Regulating C. elegans Development and Lifespan

Abstract: SUMMARY Small-molecule ligands of nuclear hormone receptors (NHRs) govern the transcriptional regulation of metazoan development, cell differentiation, and metabolism. However, the physiological ligands of many NHRs remain poorly characterized primarily due to lack of robust analytical techniques. Using comparative metabolomics, we identified endogenous steroids that act as ligands of the C. elegans NHR, DAF-12, a vitamin-D and liver-X receptor homolog regulating larval development, fat metabolism, and lifespa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
96
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 49 publications
(106 reference statements)
3
96
1
Order By: Relevance
“…We found that these genes were dispensable for DR-induced lifespan extension (Supplementary Fig. 5 and Supplementary Table 1), consistent with the notion proposed by others that DAs can be produced through an as yet uncharacterized alternative pathway 12,13 . Finally, we asked whether overproduction of DAs could enhance the response to bacterial deprivation.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…We found that these genes were dispensable for DR-induced lifespan extension (Supplementary Fig. 5 and Supplementary Table 1), consistent with the notion proposed by others that DAs can be produced through an as yet uncharacterized alternative pathway 12,13 . Finally, we asked whether overproduction of DAs could enhance the response to bacterial deprivation.…”
supporting
confidence: 74%
“…First, NHR-8 could be activated by another form of DA. This is supported by a recent report that a variety of DAs can bind with different affinities and activate DAF-12 in vivo 13 . Second, NHR-8 activation could require binding with co-activators that are present in the worm, but not in HEK293 cells.…”
supporting
confidence: 69%
“…N2 and daf-16(mu86) were grown on cholesterol or lophenolcontaining plates to obtain L3 larvae or dauer/dauer-like larvae, respectively 25 . Total RNA was isolated using the PureLink RNA Mini Kit (Ambion) and equal amounts of all samples were reverse transcribed with SuperScript III (Invitrogen) using oligo(dT) [12][13][14][15][16][17][18] primers. cDNA quality was tested using standard PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Three signalling pathways, namely the transforming growth factor (TGF)-b-like (defined by the TGF-b homologue DAF-7), insulin-like (defined by the insulin receptor homologue DAF-2) and cyclic GMP pathways 1 , converge on the activity of a nuclear hormone receptor/ transcription factor, DAF-12 (refs 10,11). DAF-12 binds sterolderived, bile acid-like molecules known as dafachronic acids (DAs) 12,13 . The last, crucial reaction in DA biosynthesis is catalysed by cytochrome P450 (CYP450) DAF-9, which produces a carboxyl group at the C-26 methyl residue of the precursor in three oxidation steps.…”
mentioning
confidence: 99%
“…Second, it is possible that NHR-8 is activated by a currently unidentified dafachronic acid metabolite. A recent study demonstrated that several forms of dafachronic acid can activate DAF-12 25 , and this may also be true for NHR-8. Finally, NHR-8 may act downstream of dafachronic acid in an indirect manner.…”
Section: The Steroid Signaling Pathway Mediates Lifespan Extension Thmentioning
confidence: 99%